2015
DOI: 10.1039/c4an01681e
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of sitagliptin using the19F-NMR method: a universal technique for fluorinated compound detection

Abstract: To expand the application scope of nuclear magnetic resonance (NMR) technology in quantitative analysis of pharmaceutical ingredients, (19)F nuclear magnetic resonance ((19)F-NMR) spectroscopy has been employed as a simple, rapid, and reproducible approach for the detection of a fluorine-containing model drug, sitagliptin phosphate monohydrate (STG). ciprofloxacin (Cipro) has been used as the internal standard (IS). Influential factors, including the relaxation delay time (d1) and pulse angle, impacting the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Besides tablets, qNMR is also employed for quantitative analysis of injection [171], suppositories [172], etc. Apart from 1 H qNMR, 19 F qNMR has also been considered as an important analytical tool in pharmaceutical analysis [176] because of the wide presence of fluorine in many drugs, 100% natural abundance of fluorine and generally low background interference. For example, disposition of fluoropyrimidine during the drug development process was investigated by 19 F qNMR [188].…”
Section: Pharmaceutical Researchmentioning
confidence: 99%
“…Besides tablets, qNMR is also employed for quantitative analysis of injection [171], suppositories [172], etc. Apart from 1 H qNMR, 19 F qNMR has also been considered as an important analytical tool in pharmaceutical analysis [176] because of the wide presence of fluorine in many drugs, 100% natural abundance of fluorine and generally low background interference. For example, disposition of fluoropyrimidine during the drug development process was investigated by 19 F qNMR [188].…”
Section: Pharmaceutical Researchmentioning
confidence: 99%
“…Nowadays, qNMR is routinely used in the identification of drugs, the determination of multicomponent drugs composition, isomeric composition determination, drug degradation studies, impurities level determination and elucidation of their structure, quality assessment, as well as counterfeit drugs determination. Commonly qNMR nuclei used in pharmaceutical applications are 1 H and 13 C. , This is partly due to the high proportion of carbon and hydrogen atoms in natural and synthetic compounds, compared to other NMR active atoms. Other studies have investigated NMR active heteroatoms, such as 19 F, 31 P, and 15 N, in the quantification and characterization of therapeutic molecules. …”
Section: Introductionmentioning
confidence: 99%
“…It is reported that 1 H‐NMR, 31 P‐NMR, and 19 F‐NMR spectroscopy have been employed in purity assessment and quantitative measurement of small molecule drugs, natural products, and body fluids . Among the series of qNMR method, 1 H‐qNMR method is one of the most common approaches due to its intrinsic advantages, including higher sensitivity and natural abundance when compared with other nuclei (e.g., 31 P and 13 C) . Therefore theoretically speaking, it has utility in quantitative determination of the compounds, provided that the isolated proton peaks are available in the NMR spectra.…”
Section: Introductionmentioning
confidence: 99%